Residues of 165 pesticides in citrus fruits using LC-MS/MS: a study of the pesticides distribution from the peel to the pulp. Issue 1 (2nd January 2020) - Calvaruso, Enza; Cammilleri, Gaetano; Pulvirenti, Andrea; Lo Dico, Gianluigi Maria; Lo Cascio, Giovanni; Giaccone, Vita; Vitale Badaco, Valeria; Ciprì, Valentina; Alessandra, Mobilia Maria; Vella, Antonio; Macaluso, Andrea; Di Bella, Calogero; et al.
Abstract: A sensitive LC–ESI-MS/MS method was developed for the determination of 165 pesticides in 50 citrus fruit samples collected in Sicily. Moreover, an evaluation of pesticides levels in the citrus layers (peel, albedo, and pulp) was carried out. The method presented acceptable trueness, precision, and linearity with LOQ of 5 μg/kg. The results obtained showed a high frequency of fungicides class pesticides in all the citrus samples examined (>95%) with the highest concentrations in the peel (4468 µg/Kg). A significant difference of concentrations was found between the layers of the citrus fruits analysed (p < 0.05). In particular, the peel and albedo present higher pesticides significantly higher than the pulp. Our findings confirming the widespread use of these substances in citrus cultivation and suggesting the importance of pesticides analysis in all the citrus fruit layers separately, considering the different interactions between the physicochemical characteristics of the matrices and the pesticides. Graphical Abstract: